Sposób istnienia utworu muzycznego - Wysocki, Michał (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2009)
The paper concerns the question deals with the issue of the mode of existence of musicalwork. The text consists of two parts. The first, describes difficulties connected with treatment ofcompositions as purely intentional objects. The second, presents the proper existence mode ofa piece of music.